Buckling failures of reserved thin pillars under the combined action of in-plane and lateral hydrostatic compressive forces. (July 2017) - Huang, Zhiguo; Dai, Xingguo; Dong, Longjun
Abstract: The reasons that pillars with small width-to-height ratios fail remain unclear. This study established a mechanical model for the buckling failure of a thin pillar subjected to compressive forces to investigate the stability of reserved thin pillars (RTPs) on both sides of mining units during barrier pillar recovery. The critical buckling stress of the thin pillar was obtained using the energy variational method, and its relationship to the aspect ratio (length-to-width ratio) was investigated. The buckling instability of RTPs can be determined by comparing the RTP stress obtained from numerical simulations with the buckling stress derived from the mechanical model.